Conduction and thermal properties of a proton conducting polymer electrolyte based on poly (epsilon-caprolactone) - Woo, H.J.; Majid, Siti Rohana; Arof, Abdul Kariem (Elsevier, 2011)
A proton conducting polymer electrolyte based on poly(epsilon-caprolactone) (PCL) complexed with different concentrations of ammonium thiocyanate (NH(4)SCN) salt has been investigated. The ionic conductivity of the solid polymer electrolyte (SPE) of pure PCL obtained at room temperature is 1.86 x 10(-11) S cm(-1). The maximum ionic conductivity achieved in the solution-cast films at room temperature is 1.01 x 10(-4) S cm(-1) for PCL incorporated with 26 wt.% NH(4)SCN. The calculated dielectric constant at selected frequencies follows the same trend as conductivity, concluding an increase in number density of ions with the salt content. DSC thermogram shows that the degree of crystallinity of PCL is reduced as more salt is accommodated in the PCL crystalline phase. The FTIR of asymmetric C N stretching mode is deconvoluted into three bands representing free ions, contact ion pairs and ion aggregates to obtain an insight on ion associations. The FTIR results show that the number of free ions become maximum at 26 wt.% NH(4)SCN. The correlation between free ions, ion aggregates and conductivity is obvious. The increase in ion dissociation improves conductivity, while the formation of ion aggregates reduces conductivity. (C) 2011 Elsevier B.V. All rights reserved.